2013
DOI: 10.1073/pnas.1313202110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic picture for conformational transition of a membrane transporter at atomic resolution

Abstract: During their transport cycle, ATP-binding cassette (ABC) transporters undergo large-scale conformational changes between inward-and outward-facing states. Using an approach based on designing system-specific reaction coordinates and using nonequilibrium work relations, we have performed extensive all-atom molecular dynamics simulations in the presence of explicit membrane/solvent to sample a large number of mechanistically distinct pathways for the conformational transition of MsbA, a bacterial ABC exporter wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
256
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(268 citation statements)
references
References 47 publications
12
256
0
Order By: Relevance
“…Instead, a defined sequence of conformational changes, occurring at different parts of the protein, is required. Recently, an elegant and detailed computational study was able to reveal such a sequence of conformational changes for a membrane transporter (42). In this context, we wondered what interactions restrained the interchain movements in the absence of the intrachain deformations.…”
Section: Dynamical Aspectsmentioning
confidence: 99%
“…Instead, a defined sequence of conformational changes, occurring at different parts of the protein, is required. Recently, an elegant and detailed computational study was able to reveal such a sequence of conformational changes for a membrane transporter (42). In this context, we wondered what interactions restrained the interchain movements in the absence of the intrachain deformations.…”
Section: Dynamical Aspectsmentioning
confidence: 99%
“…A low-energy path for interconversion between the conformations could also be identified. The free energy of the transition from the inward-open to the inward-occluded conformation indicated that the conformation as observed in the crystal structure of nucleotide free MsbA is not the most stable conformation of the membrane-inserted transporter [70,72,73]. The energy of the NBD associated inward-closed state was only slightly higher than the free energy of the global minimum of slightly separated NBDs.…”
Section: Computational Investigation Of the Conformations And Dynamicmentioning
confidence: 88%
“…Results from targeted MD or steered DM in isolation are difficult to interpret at simulations length significantly below 100 ns, because the conversion is very fast, thereby not giving the transporter enough time to react, increasing the danger of producing artefacts. The targeted MD results could not be reproduced using steered MD simulations using a much slower rate constant [70]. Unbiased simulations [71] of 100 ns, starting from the outward facing conformation, showed that the transporter was conformationally dynamic at both the extracellular site and at the level of the NBDs in the apo state.…”
Section: Computational Investigation Of the Conformations And Dynamicmentioning
confidence: 97%
See 2 more Smart Citations